Fugitives : evading and escaping the Japanese - Stahl, Bob, 1920-2003 (University Press of Kentucky, 2001)
"When the Japanese Imperial Forces invaded the Philippine Islands at the onset of World War II, they quickly rounded up Allied citizens on Luzon and imprisoned them as enemy aliens. These captured civilians were treated inhumanely from the start, and news of the atrocities committed by the enemy soon spread to the more remote islands to the south. Hearing this, many of the expatriates living there refused to surrender as their islands were occupied. Fugitives, based on the memoir of Jordan A. Hamner, tells the true story of a young civilian mining engineer trapped on the islands during the J.